Global adoption of 6-month drug-resistant TB regimens: Projected uptake by 2026. - Aastha Gupta; Sandeep Juneja; Victor Babawale; Nurov Rustam Majidovich; Norbert Ndjeka; Phuong Thi Mai Nguyen; Parpieva Nargiza Nusratovna; David Robert Omanito; Tiffany Tiara Pakasi; Yana Terleeva; Atyrkul Toktogonova; Yasir Waheed; et al. (PLoS ONE, 2024)
Background The WHO has issued a call to action urging countries to accelerate the rollout of new WHO-recommended shorter all-oral treatment regimens for drug-resistant TB (DR-TB), which remains a public-health crisis. The all-oral, 6-month BPaL/M regimen comprises 3-4 drugs: pretomanid used in combination with bedaquiline and linezolid, with or without moxifloxacin. This regimen has been recommended by the WHO for use in DR-TB patients instead of ≥9-month (up to 24-month) regimens. This study aims to project this regimen's use, along with its components bedaquiline, pretomanid and linezolid, and other treatments for DR-TB globally through 2026. It is intended to guide global health stakeholders in planning and budgeting for DR-TB interventions. Projected usage could help estimate cost of the individual components of DR-TB regimens over time. Methods Semi-structured interviews were conducted with national TB programme participants in key countries to gather intelligence on established plans and targets for use of various DR-TB treatment regimens from 2023 to 2026. These data informed development of projections for the global use of regimens and drugs. Results Consistent global growth in the use of shorter regimens in DR-TB treatment was shown: BPaLM reaching 126,792 patients, BPaL reaching 43,716 patients, and the 9-11-month all-oral bedaquiline-based regimen reaching 13,119 patients by 2026. By 2026, the longer all-oral regimen is projected to be used by 19,262 patients, and individualised treatment regimens by 15,344 patients. Conclusion The study shows BPaL/M will be used in majority of DR-TB patients by 2024, reaching 78% by 2026. However, national efforts to scale-up, case-finding, monitoring, drug-susceptibility testing, and implementation of new treatments will be essential for ensuring they are accessible to all eligible patients in the coming years and goals for ending TB are met. There is an urgent need to engage communities in capacity building and demand generation.